PENEGAKAN PERATURAN DAERAH TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH (STUDI KASUS PENEGAKAN PERSSETUJUAN BANGUNAN GEDUNG DI KABUPATEN POLEWALI MANDAR) - Armita Aminarty,; Lalu Satria Utama, (Journal of Innovation Research and Knowledge, 2025)
This research is motivated by the large number of buildings that do not have permits. The large number of violations triggers the need for enforcement of Regional Regulations (Perda) to ensure compliance with applicable regulations. Enforcement of PBG carried out by Satpol PP is very important due to the high number of violations related to building permits. This study aims to examine the enforcement of Regional Regulation Number 1 of 2024 concerning Regional Taxes and Regional Retributions, especially regarding Building Approval (PBG) by Satpol PP of Polewali Mandar Regency. This study uses a qualitative descriptive method with interviews, observations, and documentation as data collection techniques. The results of the study indicate that public awareness is still low regarding the obligation to obtain PBG, although Satpol PP has made efforts to enforce the rules, its effectiveness is hampered by the lack of socialization and community participation. This study recommends strengthening synergy between agencies, increasing legal socialization, and increasing the capacity of Satpol PP so that law enforcement is more effective